Comprehensive Nomograms Using Routine Biomarkers Beyond Eosinophil Levels: Enhancing Predictability of Corticosteroid Treatment Outcomes in AECOPD - Feng L; Li J; Qian Z; Li C; Gao D; Wang Y; Xie W; Cai Y; Tong Z; Liang L (Journal of Inflammation Research, 2024)
Lin Feng,1 Jiachen Li,1 Zhenbei Qian,2 Chenglong Li,3,4 Darui Gao,3,4 Yongqian Wang,3,4 Wuxiang Xie,3,4 Yutong Cai,5 Zhaohui Tong,2 Lirong Liang1 1Department of Clinical Epidemiology, Beijing Institute of Respiratory Medicine and Beijing Chao-Yang Hospital, Capital Medical University, Beijing, People’s Republic of China; 2Department of Respiratory and Critical Care Medicine, Beijing Institute of Respiratory Medicine and Beijing Chao-Yang Hospital, Capital Medical University, Beijing, People’s Republic of China; 3Heart and Vascular Health Research Center, Peking University Clinical Research Institute, Peking University First Hospital, Beijing, People’s Republic of China; 4Key Laboratory of Epidemiology of Major Diseases (Peking University), Ministry of Education, Beijing, People’s Republic of China; 5Centre for Environmental Health and Sustainability, Department of Health Sciences, University of Leicester, Leicester, UKCorrespondence: Lirong Liang, Department of Clinical Epidemiology, Beijing Institute of Respiratory Medicine and Beijing Chao-Yang Hospital, Capital Medical University, Beijing, People’s Republic of China, Email llrcruie@163.comPurpose: Patients with acute exacerbation of chronic obstructive pulmonary disease (AECOPD) exhibit heterogeneous responses to corticosteroid treatment. We aimed to determine whether combining eosinophil levels with other routine clinical indicators can enhance the predictability of corticosteroid treatment outcomes and to come up with a scoring system.Patients and Methods: Consecutive patients admitted with AECOPD receiving corticosteroid treatment between July 2013 and March 2022 at Beijing Chao-Yang Hospital were retrospectively analyzed. Data on patients’ demographics, smoking status, hospitalization for AECOPD in the previous year, comorbidities, blood laboratory tests, in-hospital treatment and clinical outcomes were collected. Least absolute shrinkage and selection operator (LASSO) regression and backward logistic regression were used for predictor selection, and predictive nomograms were developed. The discrimination and calibration of the nomograms were assessed using the area under the receiver operating curve (AUC) and calibration plots. Internal validation was performed using the 500-bootstrap method, and clinical utility was evaluated using decision curve analysis (DCA).Results: Among the 3254 patients included, 804 (24.7%) had treatment failure. A nomogram of eosinophils, platelets, C-reactive protein (CRP), low density lipoprotein cholesterol, prognostic nutritional index (PNI), hospitalization for AECOPD in the previous year, ischemic heart diseases and chronic hepatic disease was developed to predict treatment failure for patients with a smoking history. For patients without a smoking history, a nomogram of CRP, PNI, ischemic heart diseases and chronic hepatic disease was developed. Although the AUCs of these two nomograms were only 0.644 and 0.647 respectively, they were significantly superior to predictions based solely on blood eosinophil levels.Conclusion: We developed easy-to-use comprehensive nomograms utilizing readily available clinical biomarkers related to inflammation, nutrition and immunity, offering modestly enhanced predictive value for treatment outcomes in corticosteroid-treated patients with AECOPD. Further investigations into novel biomarkers and additional patient data are imperative to optimize the predictive performance.Keywords: chronic obstructive pulmonary disease, glucocorticoids, prediction model, least absolute shrinkage and selection operator